2003
DOI: 10.1124/jpet.103.055467
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Exposures to Heroin and/or Cadmium Alter the Rate of Formation of Morphine Glucuronides in the Rat

Abstract: After absorption, heroin is transformed into mono-acetyl-morphine and then into morphine. Morphine, in turn, is metabolized to morphine-3-glucuronide (M3G), an inactive compound, and morphine-6-glucuronide (M6G), a potent opioid agonist. Thus, changes in the rate of formation of M6G may alter the pharmacological consequences of a treatment with heroin or morphine. In this study, we investigate the effect of repeated exposures (10 daily i.p. injections) to heroin, morphine, cadmium (which has been previously sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…(as done in previous studies; Antonilli et al 2003bAntonilli et al , 2005 and after 2 h were sacrificed to obtain blood samples for the quantification of heroin, 6-monoacetylmorphine (6-MAM), morphine, M3G, and M6G (see "Microsomal preparations"), and their livers were excised to obtain microsomal preparations (see "Microsomal preparations").…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(as done in previous studies; Antonilli et al 2003bAntonilli et al , 2005 and after 2 h were sacrificed to obtain blood samples for the quantification of heroin, 6-monoacetylmorphine (6-MAM), morphine, M3G, and M6G (see "Microsomal preparations"), and their livers were excised to obtain microsomal preparations (see "Microsomal preparations").…”
Section: Methodsmentioning
confidence: 99%
“…Most important, we have shown that repeated non-contingent intraperitoneal (i.p.) injections of high doses of heroin (but not of morphine) can induce the synthesis M6G in the rat (Antonilli et al 2003b(Antonilli et al , 2005. Furthermore, microsomal preparations obtained from the livers of herointreated rats yielded, when incubated with morphine, measurable quantities of M6G, which was not detectable in microsomal preparations from rats treated with saline (Antonilli et al 2003b(Antonilli et al , 2005.…”
Section: Introductionmentioning
confidence: 97%
“…(3) the rats of third group were injected daily intraperitoneally with daily (5mg Heroin/kg b.w.) (15) .…”
Section: Experimental Protocolmentioning
confidence: 99%
“…To date, UGT2B7 is the sole enzyme reported capable of forming morphine-6-glucuronide (M-6-G) (Coffman et al, 1997), a metabolite having more potent analgesic activity than morphine. Although increasing evidence suggests that there are a number of factors that affect morphine UGT activity (Narayan et al, 1991;Ishii et al, 2001Ishii et al, , 2004Ishii et al, , 2005Antonilli et al, 2003;Takeda et al, 2005a,b), little is known about inhibitors of UGT2B7.…”
mentioning
confidence: 99%